Clinical ultrasound image standardization using histogram specification. (May 2020) - Roy, Rahul; Ghosh, Susmita; Ghosh, Ashish
Abstract: This article presents a novel ultrasound image standardization approach. This method aims to preserve the non-linear relationship in the echo-textures while ensuring the endurance in the transformed image. This is achieved by utilizing the concept of histogram specification. A reference cumulative distribution function (CDF) of a considered distribution is used to process the test images. Initially, the shape and scale parameter of the distribution are estimated for each type of echo-texture from the reference ultrasound images of a particular organ. These parameters are used to estimate the prototype parameter set. The obtained prototype parameter set, along with a distribution function, is then used to construct a reference CDF. This CDF, in turn, is used as a transfer function in the histogram specification technique for standardizing the given input image. The efficiency and stability of the proposed approach are investigated and compared with the linear scaling technique. Four measures are used to evaluate the algorithms on three data sets. The results show that the proposed approach provides better standardization of images and is invariant to the gain of the scanning device as opposed to linear scaling. Highlights: Novel ultrasound image standardization approach has been developed. Histogram specification concept has been used for standardization. Distribution parameters prototype is estimated from representative images. Reference CDF formed with prototype parameters is used as transfer function. Proposed approach for standardization is invariant to gain of scanning device.